Quizizz; An Interactive Game to Enhance Students’ Speaking - Puji Lestari; Lambok Hermanto Sihombing (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Less excited and less motivated are the problems that usually happen among the students. One of the factors that cause them become less excited and less motivated is due to teaching method. Teaching methods affect students’ outcome. The more creative the teacher is the more enjoyable the class will be. Quizizz is one of the interactive digital games that can improve students’ speaking skill. This study aims to analyze how quizizz could improve students’ ability in reading. To support their analysis, the writers employed a qualitative approach and applied the Teaching by Principle theory of H. Douglas Brown and Heekyong Lee. The scope of the study was determined by the Quizizz results of 35 students in grade XII Technical Engineering 7 at SMK Binakarya Mandiri Bekasi. The authors selected three of them as samples. Observation, interviews, and some supplementary articles were utilized to obtain data. The findings of the study revealed the viewpoints of students regarding the use of Quizizz. They concur that the Quizizz application is an engaging and entertaining way to learn English.